Varieties of Mulberries Imported From Foreign Countries and Their Description - G.A.Asenbaeva; R.P.Mambetova; E.B. Jiemuratov; Z.Yu.Ibragimova (Zien Journals, 2023)
The further development of one of the important sectors of agriculture in Uzbekistan, sericulture, requires continuous strengthening of its food base. When the mulberry tree is planted in a mix with other trees, it acts as a shelter base and protects the crops from the effects of heat and cold winds. The leaves of the planted mulberries of this type can be partially used as food for silkworms, and seeds can be taken from the fruits and seedlings can be grown. On the other hand, mulberry trees and other surrounding trees are very important in reducing the level of flood waters, improving land reclamation, and against salinity and waterlogging
Keywords: Varieties imported from Japan M.Bombycis; M.alba; M.multicalis